The leaf thermotolerance of nine tree species with varying geographic range sizes in a climate change-threatened hotspot - Reis de Brito, Carolina (2025)
The Brazilian Atlantic Forest (AF) is recognized as one of the most threatened biodiversity hotspots by global climate change. Here, we examined the leaf traits (leaf mass area, leaf thickness, and chlorophyll content) and leaf thermotolerance (T50 and TCrit) of seedlings of nine species of AF trees grown experimentally in order to foresee how extreme heat events will affect the forest’s regeneration and diversity. Based on geographic range size, the species were classified into three groups, namely, species with a restricted-range distribution (endemic to the AF), species with an intermediate-range distribution (throughout the Brazilian tropical territory), and species with a wide-range distribution (Latin America). We found that the restricted-range group did not present lower thermotolerance compared to intermediate- and wide-range species groups. Surprisingly, leaf mass area had no effect on thermotolerance indices, while chlorophyll content and leaf thickness positively influenced T50 and TCrit. Some species-specific responses to high-temperature stress deserve attention for tropical tree conservation, as is the case of Arapatiella psylophylla, a vulnerable endemic species with a very restricted-range distribution. Our results suggest that the species-specific leaf thermotolerance is an important criterion to be considered for tropical tree forest conservation in the context of global climate change.